A Systematic Review: Teacher‟s Roles in Implementing Values Education - Mohamad, Norliza; Johari Sihes, Ahmad; Mohd Bohari, Normila; Uda, Asriezam (International Journal of Psychosocial Rehabilitation, 2020)
Values education is the process of inculcating values-oriented education to students directly or indirectly, and it always occurs in a humanities course. Based on previous research, many countries have initiatives and give much attention to values in their national curriculum. The aim of this study is to analyze the existing literature on teachers’ roles in implementing values education. Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) direct the review method. Two primary databases applied in this review, namely, Web of Science (WoS) and Scopus, recognized 14 linked research articles from 2009 till 2019. From the review of selected articles, three major themes of teachers' roles in implementing values education emerged, namely, teachers as role models, teachers' competencies, and teachers' collaboration. These three significant themes further produced seven sub-themes. This systematic review hopes to afford a valuable contribution to concerned parties for the development of applications in teacher education and policies of values education in this epoch.